ChemInform Abstract: Silicon‐Based C—N Cross‐Coupling Reaction. Issue 49 (9th December 2014) - Shimizu, Kenta; Minami, Yasunori; Goto, Osamu; Ikehira, Hideyuki; Hiyama, Tamejiro
Abstract The reaction can also be applied to the cross‐coupling polymerization for the synthesis of triarylamine copolymers by reacting (XII) with (XIV) or (XVI), respectively.